Incubadoras de economia criativa: habitats multissetoriais de inovação,capacitação empreendedora e fortalecimento de redes - Carvalho, Marcos André Rodrigues de (2019)
This dissertation proposes to examine how four creative economy incubators from the state of Rio de Janeiro assisted in the development of small and medium-sized enterprises (SMEs) in the field during the period from October 2012 to October 2018. Based on substantial theoretical research regarding the concepts of creative economy and the incubation of creative enterprises, the dissertation's central argument posits that the entrepreneurship and innovation tools and dynamics offered by these four incubators, as well as the access they provided to multisectoral capacity-building environments and network-strengthening mechanisms, contributed to the growth and survival of SMEs in the creative economy sector